Implementasi Numerasi Pada Pembelajaran Bagi Guru MGMP Matematika SMA Kabupaten Semarang - Setyawati, Rina Dwi; Shodiqin, Ali; Pramasdyahsari , Agnita Siska; Endahwuri, Dhian; Agustina, Ferina (LPPM STIE Ganesha, 2025)
Pelatihan